의인성 고칼슘혈증에 의해 발생한 급성 괴사성 췌장염 1예 - 오은혜; Eun Hye Oh; 송태준; Tae Jun Song; 남광우; Kwang Woo Nam; 박도현; Do Hyun Park; 이상수; Sang Soo Lee; 서동완; Dong-wan Seo; et al. (Korean journal of pancreas and biliary tract, 2016)
급성 췌장염은 대부분의 경우 보존적 치료만으로 수 일 이내에 호전되는 경과를 보이며, 전체의 60-70%가 담석, 음주에 의해 발생하는 것으로 알려져 있다. 드물지만 고칼슘혈증에 의해서도 급성 췌장염이 발생할 수 있으며, 의인성 고칼슘혈증 또한 급성 췌장염을 유발할 수 있다. 지금까지 보고된의인성 고칼슘혈증에 의한 급성 췌장염의 증례는 모두 경증으로, 수일간의 보존적 치료 및 혈중 칼슘 농도의 정상화를 통해 합병증 없이 호전되었다. 저자들은 27세 여성에서 의인성 고칼슘혈증에 의해 발생한 급성 괴사성 췌장염과 여러 합병증에 관한 증례를 문헌 고찰과 함께 보고하고자 한다. Gallstones and alcohol consumption are well-known causes of acute pancreatitis, which usually follows a mild and self-limited course. Although extremely rare, hypercalcemia is a possible cause of acute pancreatitis. There are only few reported cases, all of which were mild and self-limited. Here we report a patient with iatrogenic hypercalcemia-induced necrotizing pancreatitis that progressed to serious adverse events such as biliary obstruction, peripancreatic fluid collection with walled-off necrosis, and acute cholecystitis. The patient was successfully treated with appropriate endoscopic and radiologic interventions, and recovered well. Korean J Pancreas Biliary Tract 2016;21(3):150-155